Effects of students' learning environment and personality on online distance learning (ODL) - Jamil, Noor Wahida; Abdul Kadir, Siti Aisyah; Mohamed Daud, Norizah; Abdul Rahim, Elin Eliana (AIP Publishing, 2023)
During the disruption of COVID-19, Malaysian Higher Education Institutions have been consistent in employing online distance learning (ODL). While the health and safety of the students and staff were prioritized, the quality of the education could not be put to a halt. For courses which could be taught online, accessibility of the students and the lecturers were critical to effective learning. Throughout the implementation of online learning in many countries, its prototypes have become the main interest of many. One of the many challenges of online learning was students' readiness to shift from face-to-face learning to non-face-to-face. This was related to students' personalities in coping with the new norm along with having a different environment, especially while being conscious of the COVID-19 pandemic. This research focused on theoretical, laboratory and project-based courses and was made to study the effect of students' learning environment and learning personality on theoretical, laboratory and project-based courses. The questionnaire was circulated to twenty-seven Information Systems Engineering (ISE) students of UiTM Malacca Campus in Jasin to analyze the issues of Online Distance Learning (ODL) during the three months of the academic session. The survey had two goals: (1) to investigate the effect of students learning environment based on three different modules of courses (theoretical, laboratory and project-based subject) and (2) to investigate the effect of students learning personality based on three different modules of courses (theoretical, laboratory and project-based subject). To achieve the first and the second goals, data were analyzed using a non-parametric statistical hypothesis testing, namely Wilcoxon Signed-Rank Test. Results of the study revealed a significant difference in the effect of ODL for the three courses on students learning personality. However, it was proven that colleagues and family were supposed to have a general perspective on online learning for the students' learning environment without considering different modules or courses taken separately. Therefore, the students' learning environment and learning personality in ODL were deemed essential aspects that successfully facilitated the teaching and learning process.